2013
DOI: 10.4161/cc.27031
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-resistant profile implies vulnerability of cancer stem cells to physiological agents, which suggests new therapeutic targets

Abstract: We have previously shown that peculiar metabolic features of cell adaptation and survival in hypoxia imply growth restriction points that are typical of embryonic stem cells and disappear with differentiation. Here we provide evidence that such restrictions can be exploited as specific antiblastic targets by physiological factors such as pyruvate, tetrahydrofolate, and glutamine. These metabolites act as powerful cytotoxic agents on cancer stem cells (CSCs) when supplied at doses that perturb the biochemical n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 23 publications
1
35
0
1
Order By: Relevance
“…Taken together, hypoxia stimulates FASN expression via HIF‐1α/SCAP/SREBP1 pathway. Besides, several recent studies reported that alteration of cellular metabolites ratios, such as NADP/NADPH, by hypoxia has also an important role in the regulation of various stem cell functions such as cell cycle and self‐renewal activities . These findings indicate that change of cellular metabolite ratios may be another pathway, in addition to the HIF1α/SCAP/SREBP1 pathway, involved in the regulation of lipid metabolism in UCB‐hMSCs.…”
Section: Discussionmentioning
confidence: 92%
“…Taken together, hypoxia stimulates FASN expression via HIF‐1α/SCAP/SREBP1 pathway. Besides, several recent studies reported that alteration of cellular metabolites ratios, such as NADP/NADPH, by hypoxia has also an important role in the regulation of various stem cell functions such as cell cycle and self‐renewal activities . These findings indicate that change of cellular metabolite ratios may be another pathway, in addition to the HIF1α/SCAP/SREBP1 pathway, involved in the regulation of lipid metabolism in UCB‐hMSCs.…”
Section: Discussionmentioning
confidence: 92%
“…Cells undergo metabolic fluctuations during differentiation under hypoxia, going between glycolysis and oxidative phosphorylation to overcome mitochondrial deficiencies [51]. It is quite possible that CSCs are able to similarly modulate redox status in order to regulate their own stem maintenance.…”
Section: Glioma Stem Cell Metabolism and Maintenancementioning
confidence: 99%
“…Change in cellular metabolite ratios may be another pathway, in addition to the HIF1a/SCAP/SREBP1 pathway, involved in the regulation of lipid metabolism in UCB-hMSCs. Some studies reported that alteration of cellular metabolite ratios, such as NADP/NADPH, by hypoxia has also an important role in the regulation of various stem cell functions such as cell cycle and selfrenewal activities [126,127].…”
Section: Molecular Mechanism Of Mscs In Hypoxic Conditionmentioning
confidence: 99%